Rečou srdca - Makaľ, Piatrus; Križanová-Brindzová, Helena: 1922-1990; Andričík, Juraj: 1937-; Gnilomedov, Vladimír; Kovačevič, Ivan Július: 1909-1979; Kovalčík, Vlastimil: 1939- (Nová sovietska tvorba, 1977)
Antológia Rečou srdca, obsahujúca ukážky z tvorby 22 bieroruských básnikov.